2017
DOI: 10.1002/chem.201702204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Water‐Soluble Palladium Nanoparticles Stabilized by Sulfonated N‐Heterocyclic Carbenes

Abstract: A strategy involving the decomposition of palladium(II) organometallic complexes with sulfonated N-heterocyclic carbene ligands leads to the formation of stable and water-soluble Pd nanoparticles. Three different methodologies (thermal decomposition, reduction under CO atmosphere, and reduction with H ) gave particles with different shapes and sizes, ranging from 1.5 to 7 nm. The structures of the organometallic intermediates and organic decomposition products were elucidated by NMR spectroscopy. To check the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 79 publications
1
49
0
Order By: Relevance
“…Recent research results suggested that hydrophilic Pd@NHCs NPs containing water‐soluble functional groups show efficient catalytic activity in neat water . Incorporation of sugar groups into Pd@NHCs NPs not only introduces chirality but also improves water solubility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research results suggested that hydrophilic Pd@NHCs NPs containing water‐soluble functional groups show efficient catalytic activity in neat water . Incorporation of sugar groups into Pd@NHCs NPs not only introduces chirality but also improves water solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Water‐soluble Pd NPs can catalyze chemical reactions in aqueous solution . After the successful synthesis and characterization of Pd@NHCs‐sugar UNPs, we were interested in investigating in detail whether these Pd@NHCs‐sugar UNPs systems are catalytically active or whether the aliphatic chains shield the active sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One way of stabilizing NPs is usually achieved with the use of ligands, which fulfill a triple function: to avoid agglomeration between the particles, to decrease the surface energy and to act as a physical barrier to reduce the diffusion of species to the particle surface. There are at least two types of well‐differentiated interactions between ligands‐NPs; On one side, there are ligands that interact covalently with the surface of the NP : this allows to control the stability of the dispersions of the steric properties of the stabilizer while imparting their characteristics and properties to the modified NPs. On the other side, there are those ligands that have charge, which stabilize the NPs by means of the Coulomb repulsion between the diffuse layers of the NP and the stabilizer …”
Section: Introductionmentioning
confidence: 99%